A rare case of Castleman's disease presenting as a pulmonary mass mimicking pulmonary malignancy - Bashyal, R; Lee, MC; Thakur, B; Singh, LN (Journal of Pathology of Nepal, 2011)
Castleman disease is a rare disorder of the lymphoid system characterized by noncancerous growths that may develop in lymph node tissues throughout the body. Most often this occurs in the neck, mediastinum, and abdomen where lymph nodes aggregate. The etiology is thought to be due to antigenic hyperstimulation of unknown origin. Two histological subtypes are described with different clinical presentations and therapeutic implications. Diagnosis is frequently accomplished only by histological analysis after surgery since no specific features have been found in imaging studies. Surgical excision is both diagnostic and curative in localized forms, whereas additional therapies are required in multicentric forms. Here we describe a case of castleman disease adjacent to the right pulmonary hilum loosely adherent to the interlobar branch of the right pulmonary artery that mimicked tuberculosis or malignancy in a 30-year-old man who underwent curative surgical removal of the mass. Keywords: Castleman disease; Pulmonary malignancy; IL-6; HHV-8; Kaposi sarcoma DOI: 10.3126/jpn.v1i1.4456 Journal of Pathology of Nepal (2011) Vol.1, 63-65